Representación y figuración en "La paz (balada futura)" de Jorge Debravo. - Campos López, Ronald (2012)
This work analyzes A Debravo's (Or Debravian) text from López-Casanova structuralist theoretical principles with the purpose to outline poem indicators, theme scheme, characterization, construction conventions, and climax structure at the representation level. On the other hand, at the imaginary level, it analyzes pragmatic and lexical semantic features from syntax to tonic words. In this way, this study sets forth an example of a methodological approach to a poem, in which the author outlines a criticism and a transforming vision of Latin America and Costa Rica socio-cultural contexts during the 60s.